Pengaruh kepercayaan, kepuasan dan pengalaman pelanggan terhadap loyalitas pelanggan pada pengguna Shopee Food Yellow Ricebox di Kota Bandung - Sondari, Tanty (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
Online service providers are required to provide a good purchasing experience to keep customers loyal. Companies need to have characteristics that can create comfort and encourage repeat purchases. Customer loyalty is influenced by several factors, including trust, satisfaction, and experience. This study aims to analyze the effect of trust, satisfaction, and experience on customer loyalty of Shopee Food Yellow Ricebox users in Bandung City. This research uses quantitative methods, descriptive analysis, verification. The data collection technique was carried out by distributing questionnaires to 127 respondents, namely consumers who have used shopee food yellow ricebox purchases. The results of this study indicate that trust (X1) has a significant effect on Customer Loyalty (Y) Satisfaction (X2) has a significant effect on Customer Loyalty (Y) and Experience (X3) has a significant effect on customer loyalty (Y). This research is expected to be able to contribute to science, especially in the field of marketing management, besides that it is expected to be a reference for further researchers and parties who have an interest in striving to increase customer loyalty.